Associação entre comprometimento da motilidade esofágica e morbidade cardíaca na Doença de Chagas - Sandra Monetti Dumont Sanches (2018)
This study was designed to assess whether alterations in esophageal motility, a surrogate marker of autonomic dysfunction, correlate with different forms of Chagas disease, and are associated with echocardiographic morbidity markers in this disease. Patients, aged between 28 - 77 years (mean 55,1 ± 11,8) were grouped in indeterminate form (FCI), dilated heart form (CCC5) and healthy controls (NCh). Twenty healthy individuals with negative serological tests for T. cruzi infection from a non-endemic area, aged 28-77 years (mean 48.2 ± 13.9), were the control group (NCh). The FCI group included 33 asymptomatic patients, aged between 39-77 years (mean of 56.0 ± 10.0), without significant electrocardiogram changes, chest radiograph and echocardiogram. The CCC5 group included 42 patients, aged between 31 - 76 years (mean of 57.6 ± 11.0) with dilated cardiomyopathy, characterized by echocardiographic findings of left ventricular dilation with impairment of systolic ventricular function. The results showed a difference in TTE values and percentage of esophageal emptying (%EE) per group (p-value <0.001). The lowest median TTE was observed for the normal group (median = 8.0), followed by the FCI (median = 16.5) and CCC5 (median = 60.0) groups. Regarding % EE, a higher median value was observed for the normal group (median = 92.3), followed by the FCI (median = 86.7) and CCC5 (median = 56.9) groups. Even after adjusting for sex and age, differences in TTE measurements and emptying by group remained (p <0.05). The results suggest that functional alterations of the esophagus, probable markers of denervation, of the disease itself, and not related to aging, and are associated with cardiac morbidity expressed by the clinical classification of Chagas disease, being more prevalent and of greater magnitude with the grade of the cardiac morbidity (NCh <FCI <CCC5). The higher the cardiac morbidity, expressed by the LVEF and LVD values, the more prevalent the functional esophageal change. This suggests a systematized and global involvement of the autonomic nervous system. Focus on now if esophageal functional impairment would be related to cardiac denervation markers.